INFLUENCE PREPROSTHETIC PREPARATION ORAL CAVITY IN PERIODONTAL DISEASES ON DENTAL STATUS AND QUALITY OF LIFE OF PATIENTS WITH PARTIAL ANODONTIA - A. R. Gorkunova; V. V. Erichev (Кубанский научный медицинский вестник, 2014)
We studied the effect of remedial and specialized training activities in oral prosthetics in periodontal diseases on dental status and quality of life of patients with partial anodontia. It was carried out a detailed dental examination 105 people, divided into 2 groups with chronic periodontal disease and without clinically significant symptoms. Based orthopantomography, CPU performance index, CPI, IGR-U data on Evdokimov tooth mobility and functional studies of dental system state program «Hamburg test» results chewing efficiency and analysis of indicators to measure the quality of life for OHIP-14 questionnaire revealed that preprosthetic preparation oral cavity with periodontal disease increases the psychological comfort and makes a significant contribution to improving the patients.